ETHNOGRAPHY OF COMMUNICATION IN MOVIE SCRIPT â€œHARRY POTTER AND THE SORCERERâ€™S STONEâ€ - Bail, Regina Veronica Piga; Matradewi, Ni Ketut Widhiarcani; Aryani, I Gusti Agung Istri (LITERA : Jurnal Bahasa Dan Sastra, 2025)
Ethnography of communication is always an interesting topic to be discussed, because when people talk to others, they may convey specific intentions to the hearers. The aims of this research were to identify the ethnography of communication factors and the functions of utterances in the Harry Potter and the Sorcererâ€™s Stone movie script. This study employed the theory entitled SPEAKING model by Hymes and the qualitative research method was applied in this study. Based on the analysis result, the charactersâ€™ utterances have various functions such as claim, birthday wish, request, order, threat, swear, apology, welcome, suggestion, prohibition, assertion, explanation, awarding points, announcing score, as well as declaring the match winner.